2009
DOI: 10.1111/j.1532-5415.2009.02498.x
|View full text |Cite
|
Sign up to set email alerts
|

The On‐Road Difficulties of Older Drivers and Their Relationship with Self‐Reported Motor Vehicle Crashes

Abstract: These findings suggest that on-road driving assessment provides useful information on older driver difficulties, with the self-directed component providing the most valuable information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…Errors concerning attention were observed and scored frequently, both to the right and to the left. Supported by previous research (Di Stefano and Macdonald, 2003;Kay et al, 2008;Wood et al, 2009), failure to check the blind spot was also a common driving error. A question that arises from our findings is: do the speeding problems cause some of the other driving errors?…”
Section: Discussionmentioning
confidence: 92%
“…Errors concerning attention were observed and scored frequently, both to the right and to the left. Supported by previous research (Di Stefano and Macdonald, 2003;Kay et al, 2008;Wood et al, 2009), failure to check the blind spot was also a common driving error. A question that arises from our findings is: do the speeding problems cause some of the other driving errors?…”
Section: Discussionmentioning
confidence: 92%
“…It is possible that the rise of advanced driver assistance systems technologies that warn drivers about issues such as lane deviation and being too close to another car will help prevent senior drivers from being involved in crashes. Previous research has found that a person giving driving directions and help to older drivers reduces the rate at which they commit errors, which the researchers noted suggests efficacy for navigation systems in the cars of older drivers (Wood et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…At each of 146 locations along the route, seven aspects of driving behavior were scored: general observation (OBS; appropriate scanning of the road environment, attention to signs and road markings, attention to other road users, and use of mirrors as appropriate); observation of blind spots (BSP), including shouldercheck for vehicles in the car's blind spot; indication (IND; appropriate use of the directional indicator); braking/acceleration (BA; appropriate speed of driving maneuvers, including driving over the speed limit or heavy, sudden braking without due cause); lane positioning (LP), including veering left or right instead of staying within the lane lines and appropriate choice of lane when turning); gap selection (GS) between the driver's vehicle and the one in front, or the gap selected by the driver when entering traffic; and approach (APP; appropriate planning and preparation in a particular driving situation or maneuver). Each location was also allocated into one of six driving situation categories: traffic-lightcontrolled intersections (TRL); one-way traffic (OWAY; straight or curved driving in a road with one-way traffic); two-way traffic (TWAY; straight or curved driving in a road with two-way traffic); give way (GWAY; entering traffic from an intersection where there is a stop or give-way sign, or where there are no traffic lights, negotiating a pedestrian crossing, or roundabout); maneuvering (MAN; including turnaround maneuvers, driving in a traffic calming area, negotiating a car park, or reversing); and merging (MER; changing lanes, entering traffic from a turn-left-with-care intersection, or pulling into or out of a parking space; see Wood et al, 2009, for further details). For statistical analyses, the number of each type of error was used as the dependent variable.…”
Section: Methodsmentioning
confidence: 99%